2014
DOI: 10.1111/jdi.12243
|View full text |Cite
|
Sign up to set email alerts
|

Role of elevated serum uric acid levels at the onset of overt nephropathy in the risk for renal function decline in patients with type 2 diabetes

Abstract: Aims/IntroductionDespite the use of intensive therapies, declining renal function is often observed during the overt nephropathy stage of type 2 diabetes. We aimed at investigating the role of serum uric acid (SUA) levels at the onset of overt nephropathy in the risk of renal function decline in type 2 diabetes patients.Materials and MethodsThe present cohort study included 290 type 2 diabetes patients who were followed from the onset of overt nephropathy. The relationship between SUA and declining renal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…In the present study, we demonstrated that higher levels of SUA were associated with declines of eGFR and identify the onset of rapid progression of CKD, furthermore at a cutoff level of > 6.5 mg/dl may link to progression of CKD in T2DM patients. Our results were consistent with previous findings, which registered that hyperuricemia seemed to be an independent risk factor for the development of incident CKD rather associated with overt nephropathy 37 and even in normalbuminuria patients with T2DM. 38 Collectively in the current study we, achieved that T2DM patients with UA ≤ 6.2 mg/dl were, younger, recently diabetic, better glycemic control, normotensive, lesser BMI, comparatively ideal TG/HDL-C, lower prevalence of early and overt nephropathy and preserved GFR.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, we demonstrated that higher levels of SUA were associated with declines of eGFR and identify the onset of rapid progression of CKD, furthermore at a cutoff level of > 6.5 mg/dl may link to progression of CKD in T2DM patients. Our results were consistent with previous findings, which registered that hyperuricemia seemed to be an independent risk factor for the development of incident CKD rather associated with overt nephropathy 37 and even in normalbuminuria patients with T2DM. 38 Collectively in the current study we, achieved that T2DM patients with UA ≤ 6.2 mg/dl were, younger, recently diabetic, better glycemic control, normotensive, lesser BMI, comparatively ideal TG/HDL-C, lower prevalence of early and overt nephropathy and preserved GFR.…”
supporting
confidence: 83%
“…Generally, these results appear compatible with other studies which found, SUA concentration was associated with microalbuminuria and increased progression to overt nephropathy in patients with T2DM 36 as well SUA levels, even within the normal range > 6.3 mg/dl can predict the onset of overt nephropathy. 37 Overt nephropathy resulted in an increased risk for declining renal function in T2DM. The role of UA in patients with T2DM is still not well studied, particularly in association with declining renal function.…”
mentioning
confidence: 99%
“…Recent studies have shown that elevated SUA levels may be associated with the faster progression of diabetic kidney disease [28][29][30]. The present data indicate that these past findings may be applicable to early stage diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 64%
“…SUA is known to be associated with disease progression in the early stage of diabetic nephropathy [17,58] . We found that the progression of renal dysfunction in patients with type 2 diabetic overt nephropathy with an SUA concentration of ≥ 6.3 mg/dL carries a poor prognosis, even though their SUA range is considered high-normal [59] . Our data shows the association between UA and disease progression is independent of diabetic control in multivariate analysis.…”
Section: Nephropathymentioning
confidence: 98%
“…Through inhibition of XDH/XO activity, cytokine-induced neudependent risk factor for renal dysfunction, even after adjustments for confounding factors. Furthermore, even high-normal SUA levels accelerated renal dysfunction in T2DM patients [17,[59][60][61][62] . UA is lowered in diabetes mellitus (DM) due to hyperfiltration [50] , but decreased UA excretion during renal dysfunction raises SUA levels.…”
Section: Atherosclerosis and Xdh/xo In Monocytes/macrophagesmentioning
confidence: 99%